2023
DOI: 10.3390/pharmaceutics15020423
|View full text |Cite
|
Sign up to set email alerts
|

Development of Janus Particles as Potential Drug Delivery Systems for Diabetes Treatment and Antimicrobial Applications

Abstract: Janus particles have emerged as a novel and smart material that could improve pharmaceutical formulation, drug delivery, and theranostics. Janus particles have two distinct compartments that differ in functionality, physicochemical properties, and morphological characteristics, among other conventional particles. Recently, Janus particles have attracted considerable attention as effective particulate drug delivery systems as they can accommodate two opposing pharmaceutical agents that can be engineered at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 142 publications
(165 reference statements)
0
7
0
Order By: Relevance
“…By altering the interaction energy between particles, stable hybrid networks can be formed to offer precise control over the properties of biological materials for various applications such as drug delivery, [ 10–13 ] tissue engineering, [ 14,15 ] and biosensing. [ 20 ] Here, we tune colloidal surface forces in the dispersions of one and two particulate species by altering the dispersion ionic strength and studying the spatial organization of colloidal particles on a glass substrate to deposit self‐assembled particulates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By altering the interaction energy between particles, stable hybrid networks can be formed to offer precise control over the properties of biological materials for various applications such as drug delivery, [ 10–13 ] tissue engineering, [ 14,15 ] and biosensing. [ 20 ] Here, we tune colloidal surface forces in the dispersions of one and two particulate species by altering the dispersion ionic strength and studying the spatial organization of colloidal particles on a glass substrate to deposit self‐assembled particulates.…”
Section: Introductionmentioning
confidence: 99%
“…[9] In recent years, particle-mediated self-assembly has attracted significant attention in designing programmable biodegradable materials with tailored properties. Specifically, this technique has been extensively studied in developing drug delivery systems with precisely controlled release rates and targeting capabilities, [10][11][12][13] as well as scaffold materials for tissue engineering with desired mechanical properties. [14,15] Hence, the development of bioinspired hybrid particulate networks through particle-mediated self-assembly has provided a promising approach for enhancing the mechanical and biodegradation properties of both biological and synthetic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rational design of Janus particles with tunable morphology, size, and composition is still the core problem of current research. Moreover, dual-asymmetry Janus particles with concave and convex structures are valued in many special fields because of their special composition. Our group successfully prepared dual asymmetric Janus silica particles by the hexadecyltrimethylammonium bromide- and octadecylamine-assisted Pickering emulsion strategy, which promoted the monolayer alignment of micron-sized silica particles at the toluene–water interface . Roghani-Mamaqani et al fabricated dumbbell- and cauliflower-shaped Janus particles by different feeding ways, which were utilized for loading and release of drugs such as ibuprofen.…”
Section: Introductionmentioning
confidence: 99%
“…14 Self-assembly of magnetic Janus beads was investigated by Hatton et al, who showed the reversible self-assembled constitution of these beads by changing the pH. 15 Drug delivery, 16 biological inquiry, 17 and virtual device manipulation 18 are a few of the uses of these controlled self-assembled structures.…”
mentioning
confidence: 99%